Students’ Construction on Political Space Openness for Generation Z (Forum Ilmu Sosial, 2022)
Generation Z has had enough age to join the political space. They have great potential in politics. Political parties open space for the public to participate in general election contestations as legislative candidates. Generation Z is no exception. However, the problem is when Generation Z has no interest in entering the political space. This can be motivated by the younger generation, both millennials and generation Z, who are less interested in political issues. And the absence of space and desire to channel their political desires and aspirations. This study aims to determine students' views as Generation Z and identify the processes of externalization, objectification, and internalization of the opening of political space. The method applied is a qualitative method. The theoretical perspective used is the social construction theory of Peter L. Berger and Thomas Luckmann. The results of the study show that students as Generation Z have determined their political position in choosing candidates. However, they are not interested enough or have not had the full opportunity to join a political party).